A campanha do Referendo Constitucional Venezuelano de 2007 e a fronteira discursiva entre o "SI" e o "NO" - Sapper, Alexandre Neves (2009)
The present work aimed to identify, with the contribution of discourse theory of Laclau and Mouffe, the emergence of antagonistic poles of the last referendum held in Venezuela, with the guiding hypothesis of this study to claim that it is possible to put the "Si "was not necessarily in favor of Chavez, the same as the "No" was not made against the president of Venezuela, making plausible the personifying the manifestation of the poles (which is most evident in the formation of the "No"), demonstrations these focused on the significant conditional on each training antagonistic ("Si and "No"). The procediment of this research occurred with the theoretical study of the literature relevant to the subject and subsequent analysis of the speeches constitutional referendum occurred in Venezuela in 2007.